ANALISIS KEGAGALAN PERUSAHAAN BLACKBERRY DENGAN MENGGUNAKAN MODEL MANAJEMEN PERUBAHAN SATIR - Daniel CS, Wiltasar; Rizky, Irgi Saeful; Zalzabyella, Arzella; Lunanda, Zahra Aurela; Oktaviana, Narumi (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The ability of an organization to adapt becomes important in the modern era full of dynamic changes, as seen in the Blackberry failure. In the context of Blackberry change management, this study examines the failure through the Satir Change Model approach, which emphasizes the emotional dynamics and individual behavior during the change process. These stages include Status Quo, Resistance, Chaos Integration, and New Status Quo. This study uses a qualitative approach based on case studies. It is hoped that this study will provide knowledge to other organizations on how to manage change effectively and sustainably.